2021
DOI: 10.1136/bmjsrh-2020-200975
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted prevention: condom and contraception access and use among young adults during the initial months of the COVID-19 pandemic. An online survey

Abstract: BackgroundThe initial response to COVID-19 in the UK involved a rapid contraction of face-to-face sexual and reproductive health (SRH) services and widespread use of remote workarounds. This study sought to illuminate young people’s experiences of accessing and using condoms and contraception in the early months of the pandemic.MethodsWe analysed data, including open-text responses, from an online survey conducted in June–July 2020 with a convenience sample of 2005 16–24-year-olds living in Scotland.ResultsAmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 9 publications
10
86
1
Order By: Relevance
“…As our survey was conducted between June-July 2020, we asked young people whether COVID-19 related social distancing measures had made any difference to their access to, and use of, condoms and contraception. These findings are described more fully elsewhere [7].…”
supporting
confidence: 61%
“…As our survey was conducted between June-July 2020, we asked young people whether COVID-19 related social distancing measures had made any difference to their access to, and use of, condoms and contraception. These findings are described more fully elsewhere [7].…”
supporting
confidence: 61%
“…We do not have information on why women found it harder to access contraception; however, a recent online study from Scotland reported several factors impacting access to contraception during the COVID-19 pandemic. 12 These include a lack of clarity about the legitimacy of trying to access SRH services during a pandemic, uncertainty about which SRH services are still available, limited GP appointments, challenges to contraceptive prescribing, and closure of usual points of access to free condoms within community settings. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 12 These include a lack of clarity about the legitimacy of trying to access SRH services during a pandemic, uncertainty about which SRH services are still available, limited GP appointments, challenges to contraceptive prescribing, and closure of usual points of access to free condoms within community settings. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Study findings reinforce the importance of ensuring that young people have continued access to sexual and reproductive health care during the ongoing pandemic. While some youth have continued to be sexually active, due to shelter-in-place restrictions and limitations to inperson clinical services, contraception and other services have become more difficult to access [41][42][43]. Many healthcare providers have quickly adapted to offer services through telemedicine during the pandemic, although more research is needed to improve the reach and appropriateness of telemedicine among adolescents and young adults [44,45].…”
Section: Discussionmentioning
confidence: 99%